Representasi Dakwah dalam Novel Ayat-Ayat Cinta 2 Karya Habiburrahman El Shirazy - Kurnia Maulida; Chelsy Yesicha (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2019)
Habiburrahman El Shirazy's novel entitled Ayat-Ayat Cinta 2, there are parts ofthe story that show a change in the attitude of the character who initially hated Islam tobe positive towards Islam. This is of course due to the da'wah process which is not onlythrough oral and written but also attitudes and actions that show good Islam. Thepurpose of this study was to determine the representation of da'wah in the novel AyatAyatCinta2seenbasedonthestorylineandcharacters,aswellastheauthor'sextrinsic elementinrepresentingda'wahinthenovel.Thisresearchusesdescriptivemethodusing narrative analysis of Tzvetan Todorov and Algirdas Greimas, as the analysis knife.Furthermore it is known that most of the da'wah shown in this novel was carried out byFahri. Fahri does all kinds of da'wah. Da'wah can be done by anyone and the personwho does this da'wah is someone who knows and understands what should be done theninvites others to do the same. The author's extrinsic element in representing da'wah in the novel Ayat-Ayat Cinta 2, namely, biography or rather the educational background, personal experience, and social conditions seen and experienced by the author.